Biological nitrogen removal from low carbon wastewater - Kosgey, Kiprotich; Zungu, Phumza Vuyokazi; Bux, Faizal; Kumari, Sheena (Frontiers in Microbiology, 2022)
Nitrogen has traditionally been removed from wastewater by nitrification and denitrification processes, in which organic carbon has been used as an electron donor during denitrification. However, some wastewaters contain low concentrations of organic carbon, which may require external organic carbon supply, increasing treatment costs. As a result, processes such as partial nitrification/anammox (anaerobic ammonium oxidation) (PN/A), autotrophic denitrification, nitritation-denitritation and bioelectrochemical processes have been studied as possible alternatives, and are thus evaluated in this study based on process kinetics, applicability at large-scale and process configuration. Oxygen demand for nitritation-denitritation and PN/A is 25% and 60% lower than for nitrification/denitrification, respectively. In addition, PN/A process does not require organic carbon supply, while its supply for nitritation-denitritation is 40% less than for nitrification/denitrification. Both PN/A and nitritation-denitritation produce less sludge compared to nitrification/denitrification, which saves on sludge handling costs. Similarly, autotrophic denitrification generates less sludge compared to heterotrophic denitrification and could save on sludge handling costs. However, autotrophic denitrification driven by metallic ions, elemental sulfur (S) and its compounds could generate harmful chemicals. On the other hand, hydrogenotrophic denitrification can remove nitrogen completely without generation of harmful chemicals, but requires specialized equipment for generation and handling of hydrogen gas (H2), which complicates process configuration. Bioelectrochemical processes are limited by low kinetics and complicated process configuration. In sum, anammox-mediated processes represent the best alternative to nitrification/denitrification for nitrogen removal in low- and high-strength wastewaters.